A study of the influence of novel scan strategies on residual stress and microstructure of L-shaped LPBF IN718 samples. (February 2022) - Pant, Prabhat; Salvemini, Filomena; Proper, Sebastian; Luzin, Vladimir; Simonsson, Kjell; Sjöström, Sören; Hosseini, Seyed; Peng, Ru Lin; Moverare, Johan
Graphical abstract: Highlights: Re-melting scan strategy reduced residual stresses magnitude by approximately 25%. Total fill strategy led to strong crystallographic fiber texture 〈0 0 1〉 // scan direction. Defects (>50 µm) at the interface between the sections were observed for sectional strategies. Abstract: Process parameters in laser-based powder bed fusion (LBPF) play a vital role in the part quality. In the current study, the influence of different novel scan strategies on residual stress, porosities, microstructure, and crystallographic texture has been investigated for complex L-shape parts made from nickel-based superalloy Inconel 718 (IN718). Four different novel scanning strategies representing total fill, re-melting, and two different sectional scanning strategies, were investigated using neutron diffraction, neutron imaging, and scanning electron microscopy techniques. These results were compared with the corresponding results for an L-shape sample printed with the conventional strategy used for achieving high density and more uniform crystallographic texture. Among these investigated novel strategies, the re-melting strategy yielded approximately a 25% reduction in surface residual stress in comparison to the reference sample. The other two sectional scanning strategies revealed porosities at the interfaces of the sections and due to these lower levels of residual stress were also observed. Also, variation in crystallographic texture was observed with different scan strategies.